SEATROBS: Development of Sealife Travel & Tour Online Booking System Using Usability Theory - Mazita, Mokhtar; NorHasnul Azirah, Abdul Hamid; Nurul Athirah, Ahmad Nazri (UTeM Press, 2022)
The travel and tour industry is one of the world’s largest industries in Malaysia, where businesses in this industry always seek advanced technology to face intense competition. Sealife Travel and Tour Sdn. Bhd. is one of them, where the owner of this company is seeking a system that can cater to their problems due to the implementation of a manual system in the customers’ booking process. Therefore, this research aims to develop a Sealife Travel Online Booking System (SEATROBS) for the company. The Adapted Waterfall model has been used as a methodology, and usability heuristics had been used as a theory to guide the development of this system. Keywords: online booking system; travel agency; usability theory